40Ar/39Ar geochronology and revised stratigraphy of the late Eocene Taxco volcanic field, southern Mexico. (November 2017) - Hernández-Vargas, José Juan; Martiny, Barbara M.; Morán-Zenteno, Dante J.; Pérez-Gutiérrez, Rosalva; López-Martínez, Margarita
Abstract: The late Eocene Taxco volcanic succession constitutes an important record of explosive silicic volcanism in the north-central Sierra Madre del Sur of southern Mexico. Detailed stratigraphic studies with age dating of individual units in this area were lacking in spite of it being an important mining district. Re-examination of the stratigraphy together with geochronologic studies were used to define the eruptive style and constrain the age of the main episode of silicic activity. Major element data show a rhyolitic composition for all the units analyzed. The volcanic succession records silicic explosive eruptions during which ash-flows, surge and ash-fall deposits, lava flows and domes were emplaced. Earliest activity was contemporary with the end of sediment accumulation of the continental Balsas Group. The first main episode of volcanic activity produced massive, moderately welded, crystal-poor lithic ignimbrites and ash-fall deposits, which evolved into crystal-rich, densely welded ignimbrites with flattened pumice clasts (San Gregorio ignimbrite) thought to represent erupted mush related to caldera collapse during emptying of the magma chamber. A second episode of non-welded, vapor-phase, indurated ignimbrites and surge deposits (Sombrerito ignimbrite), which are rich in pumice but crystal-poor, suggest volatile-rich magmatism and replenishment of the magma chamber by evolved magmas. Rhyolite emplaced in volcanic units of both episodes point to volatile-poor magmas during which rhyolite flows and domes formed. 40 Ar/ 39 Ar dating of the units, from the crystal-rich San Gregorio ignimbrite near the base of the succession to rhyolites at the top, has constrained the age of the Taxco volcanic field to a relatively short period between ∼36 and 34.5 Ma. Most of the sanidine ages obtained are indistinguishable within error: the densely welded San Gregorio ignimbrite (34.75 ± 0.26, 35.22 ± 0.26 Ma) and the overlying Peral ignimbrite (35.29 ± 0.41, 35.68 ± 0.20). Plagioclase of the Tenería Formation rhyolites gave the same age within error (34.45 ± 1.10, 34.94 ± 0.34 Ma), documenting the end of the main volcanic episodes. A younger plagioclase age of 30.89 ± 1.45 Ma of a dome near Tetipac gives evidence of later silicic magmatism in the area. The source of the ignimbrites of the Taxco region is inferred to be located in the Tenería area, where abundant rhyolite dome structures seem to obliterate the main caldera structure. Differences in age, mineralogy and geochemistry between the Taxco succession and nearby volcanic zones where caldera structures have been identified preclude sources in these areas. Highlights: The stratigraphy and chronology of the Taxco volcanic field is revised. Magmatism is predominantly silicic, with an early stage of intermediate volcanism. We infer the episode of crystal-rich pyroclastic emissions are associated with a caldera collapse. Subsequent crystal-poor, volatile-rich pyroclastic activity might be linked to silicic magma recharge. Paleogene silicic volcanic activity occurred mainly from ∼36 to 34.5 Ma.